Studi Sanitasi RSU “ Dr. Koesnadi ” Kabupaten Bondowoso - Haris Ahmadi; Isa Ma’rufi (Multidisciplinary Journal, 2021)
The quality of the Hospital Environment (RS) that is good in terms of physical, biological, chemical, and social will make it a place of health services that can guarantee the maintenance and improvement of the health status of the community. Hospitals are places where there is close contact between humans (visitors, patients, and the community) with the surrounding environment, then the hospital must comply with the sanitation quality standards that have been regulated in the applicable law. Hospital health worthiness is carried out to prevent things that can cause problems in decreasing the quality of sanitation and the quality condition of hospital sanitation facilities, such as waste, clean water media, drinking water, food, air media, infrastructure and building quality as well as vectors/animals carrying disease. resulting in the transmission of disease in the hospital itself. The purpose of the study was to find out the description of the hospital's health-worthy quality which was determined through the achievement of standard environmental quality standards and fulfilled other health requirements at the "Dr. Koesnadi” Hospital Bondowoso. This type of research is classified as descriptive evaluative, namely wanting to obtain an explanation of the sanitary conditions in the hospital. The research subject is “dr. Koesnadi” Hospital Bondowoso and his environment in accordance with the reference to the use of the Hospital Environmental Health Inspection Form (IKL) in accordance with the Minister of Health Regulation No. 007/Menkes/Per/II/2019. The results of the research, in general the results of environmental supervision and inspection are very good (total score of 8,840) but still need improvement on variables, especially air health media on aspects of lighting quality standards and certain spaces, ready food health in the certificate process. Healthy Catering Services Category B and measuring vector density numbers, especially those that are still being carried out so that it will affect vector control activities. Keywords: Hospital, environmental quality, hospital category